2018
DOI: 10.1093/biolre/ioy020
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific requirement for GSK3α in sperm for male fertility†

Abstract: Glycogen synthase kinase 3 (GSK3) is a highly conserved protein kinase regulating key cellular functions. Its two isoforms, GSK3α and GSK3β, are encoded by distinct genes. In most tissues the two isoforms are functionally interchangeable, except in the developing embryo where GSK3β is essential. One functional allele of either of the two isoforms is sufficient to maintain normal tissue functions. Both GSK3 isoforms, present in sperm from several species including human, are suggested to play a role in epididym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…20,21,23 The sperm phenotypes of the KO are similar. The two signaling enzymes, GSK3α and PPP3R2, are essential for male fertility: deletion of either corresponding genes results in male infertility.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…20,21,23 The sperm phenotypes of the KO are similar. The two signaling enzymes, GSK3α and PPP3R2, are essential for male fertility: deletion of either corresponding genes results in male infertility.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, it has been reported that the luminal fluid of caput has threefold higher calcium concentration than the caudal region of the epididymis. 20 The next part of our study was examination of the relationship between sperm calcineurin and GSK3. [59][60][61] A key conclusion of our study is that high calcineurin activity in caput sperm followed by a decline in its activity in caudal sperm is a key physiological requirement for epididymal sperm maturation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations